Peace among Muslims: Religious Obligation or Political Expediency? (American Journal of Islam and Society, 2011)
Peace is seen as a sociopolitical value whose permanent realization keepseluding humanity, despite constant efforts (at least for the past century) forit to prevail permanently. For Muslims, peace1 is not just a sociopoliticalimperative; it is also a religious obligation. So any attempts to achieve itat anytime (be it among Muslims, or between them and their non-Muslimenemies) must be considered an act of obedience to God, who enjoinedthem, on several occasions in the Qur’an (for example, 8:61), to strivetoward peace. In this editorial, I will highlight only peace amongMuslims ...